Determinants and growth effects of foreign direct investment - Kristian Uppenberg; Armin Riess (EIB Papers, 2004)
Focussing on Europe, this paper starts with reviewing the main determinants of foreign direct investment (FDI); a key observation is that economic policies and non-policy factors contribute equally to the direction of FDI flows. The paper then examines the growth-FDI nexus: while a strong positive correlation between inward FDI and economic growth exists, at least in the more advanced EU-15 economies it is not clear whether the causality runs from FDI to growth or vice versa; in the countries of Central and Eastern Europe (CEE) there is stronger evidence that FDI has boosted growth during the transition period, partly by augmenting domestic investment; that said, evidence of technology spillovers (a potentially important channel for FDI to boost growth) is harder to find in CEE than in developed economies. The paper finally argues that growth-enhancing policies in general are more promising than specific support for FDI.
Keywords: 330; Direktinvestition; Wirtschaftswachstum; Spillover-Effekt; EU-Staaten; Osteuropa